CLINICAL AND IMMUNOLOGICAL FEATURES OF ROTAVIRUS GASTROENTERITIS IN CHILDREN INFECTED WITH HERPES VIRUSES (World Science, 2019)
The article presents the results of a comparative analysis of clinical and immunological parameters in children with rotavirus gastroenteritis without background infection and those infected by herpes viruses. It was established that in children with rotavirus infection (RVI) on the background of infection by herpes viruses occurs with less pronounced symptoms of intoxication and a less frequency of vomiting at the onset of the disease, in combination with longer duration (more long period) of fever and diarrheal syndrome. Such features are probably associated with the formation of a hypergical regime of the functioning of the immune response in the group of patients with background infection by herpes viruses, in contrast to patients with mono- RVI, in whom the immune system functions in a normal compensation mode.